The influence of biofuels, economic and financial factors on daily returns of commodity futures prices - Bernardina Algieri (University of Bonn, Center for Development Research (ZEF), 2014)
Biofuels production has experienced rapid growth worldwide as one of several strategies to promote green energy economies. Indeed, climate change mitigation and energy security have been frequent rationales behind biofuel policies, but biofuels production could generate negative impacts, such as additional demand for feedstocks, and therefore for land on which to grow them, with a consequent increase in food commodity price. In this context, this paper examines the effect of biofuels and other economic and financial factors on daily returns of a group of commodity futures prices using Generalized Autoregressive Conditional Heteroskedasticity (GARCH) family models in univariate and multivariate settings. The results show that a complex of drivers are relevant in explaining commodity futures returns; more precisely, the Standard and Poors (S&P) 500 positively affects commodity markets, while the US/Euro exchange rate brings about a decline in commodity returns. It turns out, in addition, that energy market returns are significant in explaining commodity returns on a daily basis, while monetary liquidity does not. Finally, the GARCH model has shown that current variance is influenced more by its past values than by the previous days shocks, and there is high persistence, meaning that variance slowly decays and prompts a sluggish 'revert to the mean' The multivariate BEKK framework confirms the results of the univariate setting.
Keywords: C58; G15; Q14; Q43; 330; futures returns; biofuels; univariate and multivariate GARCH